SEASONAL VARIATION IN DISSOLVED CARBOHYDRATE (DCHO) CONTENT IN THREE FRESHWATER PONDS - Vijayaraghavan, Sumitra (Indian Journal of Fisheries, 2011)
Considerable work has Been done on the dynamics of DCHO from temperate regions. Some of the contributions are those of Allen (1956) Guillard and Wangersky (1958), Nalewajo et al. (1963) and Walsh (1965 and 1966). However, practically no information is available on this important constituent from the tropics. Fogg (1962) stated that the rate of turnover of organic acids and carbohydrates is probably high enough to Ue ecologically important. In the present paper, therefore, an attempt has been made to study the seasonal variations in DCHO in relation to some of the physico-chemical and biological factors in three tropical ponds.